Design and Development of a Web-Based Public Information System for Community Complaint Services at the Regional House of Representatives (DPRD) of West Java Province - Anggia Putri Deniyanti; Rini Suwartika Kusumadiarti; Candra Mecca Sufyana (Dinasti Information and Technology, 2026)
Advancements in information technology have accelerated digital transformation across various sectors, including public services. The Regional House of Representatives (DPRD) of West Java Province holds a strategic role in accommodating and responding to public aspirations and complaints. However, the existing manual complaint management process presents significant challenges, such as inefficiencies in operations, limited transparency, and potential inaccuracies in data handling. To address these issues, this study proposes the design and development of an integrated, web-based public complaint information system. The system is developed using the structured Waterfall model, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. PHP and MySQL serve as the core technologies for development. Results from black-box testing indicate that all system functionalities perform as expected. The system allows users to register, submit complaints, and track their status in real time, while administrators can efficiently manage and respond to complaints through an online interface. This solution is expected to strengthen communication between the public and the DPRD and to foster greater public participation in government accountability and oversight.